Efektifitas Media Roda Bangun Datar dengan Model Kooperatif Tipe Think Talk Write - Rahman, Abdul; Bernard; Sutarman, Annisa Audiningrum (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
The kind of this research is pre experiment research that aims to find out the effectiveness of Wheel Plane Media With Think Talk Write on The Topic of Triangle and Square of Grade VII Students of SMP. The effectiveness of learning can be seen from the results of students’ learning achievement, students’ activities, and students’ responses after the implementation of learning. This research was conducted in SMP with experimental unit consisting of grade VII students of SMP for giving treatment with the design of the research is one group pretest posttest design. The number of this research was 30 students. This research was carried out during 7 meetings which consist of 1 meeting of the pretest, 1 meeting of the posttest and 5 meetings of mathematics learning by using wheel plane media with Think Talk Write model. Data of students’ activities that related to cooperative skills and the teachers’ activities in the learning process have 1 observer that is the teacher of the class. The data were analyzed by using descriptive statistical analysis to describe the students’ learning achievement, students’ activities, teacher’s activities in teaching process and students’ responses. There was a significantly increase of students’ learning achievement after implementation of wheel plane media wiyh Think Talk Write model on triangle and square material. From the results of this research it can be concluded that wheel plane media with Think Talk Write model of grade VII students of SMP in effective category.